Effects of a golf swing intervention on senior golfers` ball striking and motivation to play golf - Kanwar, K. D.; Mann, M. D. (International Journal of Sports Science & Coaching, 2018)
Several golf swing movements have been correlated with the production of club speed in skilled golfers. However, less skilled golfers, such as senior golfers, may not be capable of many of those movements. One golf swing—Minimalist Golf Swing—reduces the downswing range of motion through which a golfer`s body must move to reach the impact positions seen in skilled golfers. The purpose of this study was to assess whether the MGS could improve senior golfers` ball flight and consistency, and increase their motivation to play golf. Twenty-two seniors (16 males, 6 females), aged 54-81, participated in an 11-session study comprising pretest, intervention, and posttest sessions. During the test sessions, participants hit 20 shots with each of their own 6-iron and driver clubs. Ball movement immediately after impact was measured using a camera-based ball launch monitor. Participants` motivation to play golf before and after the intervention was assessed using the Sports Motivation Scale II. A mixed effects model was used for the statistical analysis of this repeated measures study, in which participants served as their own controls. Statistically significant per-session results were an increase in the ball`s speed (6-iron and driver) and trajectory (6-iron), and a change in direction (both clubs) from left to slightly right (for right handed golfers). Consistency of ball flight, total motivation and intrinsic motivation increased slightly post-intervention, while amotivation decreased, none significantly. Therefore, some senior golfers can improve ball flight, consistency, and motivation to play golf after six MGS training sessions.